2023
DOI: 10.3389/fpsyg.2023.1113142
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional personality pathology and disordered eating in young adults: measuring the DSM-5 alternative model using the PID-5

Abstract: IntroductionThe Personality Inventory for DSM-5 (PID-5) is a self-report measure of personality pathology designed to measure pathological personality traits outlined in the DSM-5 alternative model of personality disorders. Within the extensive literature exploring the relationship between personality and disordered eating, there are few that explore the relationship between the PID-5 and disordered eating behaviours in a non-clinical sample of males and females: restrictive eating, binge eating, purging, chew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Although UC personality type has previously been linked to increased binge eating and purging behaviour [ 9 , 30 ], the relationship between personality type and other eating behaviours has not been explored previously. For example, past research has identified a relationship between compulsive exercise and elevated Neuroticism [ 80 , 81 ] and Extraversion [ 81 ], and chewing and spitting behaviour has previously been related to impulsivity [ 50 , 69 ]. What can be implied is that elevated extraversion and impulsivity might put UC individuals at higher risk of compulsive exercise and chewing and spitting, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although UC personality type has previously been linked to increased binge eating and purging behaviour [ 9 , 30 ], the relationship between personality type and other eating behaviours has not been explored previously. For example, past research has identified a relationship between compulsive exercise and elevated Neuroticism [ 80 , 81 ] and Extraversion [ 81 ], and chewing and spitting behaviour has previously been related to impulsivity [ 50 , 69 ]. What can be implied is that elevated extraversion and impulsivity might put UC individuals at higher risk of compulsive exercise and chewing and spitting, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Data from this study have previously been described elsewhere [ 50 , 69 ]. In order to attract prospective participants, advertisements providing a brief overview of the goals of the study and anticipated time commitment were posted on social media.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, we compared the structures of the DSM-5 and ICD-11 systems to predict scores on the dimensional measures of both mental disorders. A few studies address the overlap between maladaptive traits and BED or BSD (Gilmartin et al, 2023;. Some reports have also shown that some domains of the DSM-5 (Negative Affectivity, Disinhibition, and Psychoticism) and the ICD-11 (Negative Affectivity and Disinhibition) systems are significantly related to the symptoms of BED and BSD Sellbom et al, 2022;Stricker et al, 2022).…”
Section: Current Studymentioning
confidence: 99%